Implementing The Sharia Marketing Mix (7P) In The Digital Umrah Travel Industry A Case Study Of PT Auva Eqtena Nahdha - Anisah Fithriyyah Salsabila; Saqofa Nabilah Aini; Mustofa Mustofa (Yayasan Rahmat Islamiyah, 2026)
This study aims to analyze the digital Islamic marketing strategy implemented by PT Auva Eqtena Nahdha (Auva Tour) to attract consumer interest in Umrah pilgrimage services. The study is motivated by the increasing public enthusiasm for performing Umrah post-COVID-19 pandemic, which has intensified competition in the Sharia-based travel industry. This research employs a qualitative method with a descriptive approach and a single-case study design, involving in-depth interviews, observations, and documentation of Auva Tour’s digital and Sharia-compliant marketing practices. The results indicate that the implementation of a marketing strategy based on the 7P mix (Product, Price, Place, Promotion, People, Process, Physical Evidence) enhances consumer trust, comfort, and loyalty.